Textual, Musical, and Theatrical Adaptations of Boiardo's Orlando Innamorato. (3rd April 2019) - Cavallo, Jo Ann
ABSTRACT: Boiardo's Orlando Innamorato has been reimagined through the centuries in prose and verse rewritings, in operatic, melodramatic, theatrical, and cinematic adaptations, and especially in popular traditions such as puppet theatre, epic maggi (folk operas), and recitations by singers and contastorie . This essay offers a diachronic panorama of textual, musical, and theatrical adaptations of Boiardo's romance epic from the early sixteenth century to the present. Attention is given to both elite and popular culture.